Heterozygous truncation mutations of the SMC1A gene cause a severe early onset epilepsy with cluster seizures in females: Detailed phenotyping of 10 new cases. (6th February 2017) - Symonds, Joseph D.; Joss, Shelagh; Metcalfe, Kay A.; Somarathi, Suresh; Cruden, Jamie; Devlin, Anita M.; Donaldson, Alan; DiDonato, Nataliya; Fitzpatrick, David; Kaiser, Frank J.; Lampe, Anne K.; Lees, Melissa M.; et al.
Summary: Objective: The phenotype of seizure clustering with febrile illnesses in infancy/early childhood is well recognized. To date the only genetic epilepsy consistently associated with this phenotype is PCDH19, an X‐linked disorder restricted to females, and males with mosaicism. The SMC1A gene, which encodes a structural component of the cohesin complex is also located on the X chromosome. Missense variants and small in‐frame deletions of SMC1A cause approximately 5% of Cornelia de Lange Syndrome (CdLS). Recently, protein truncating mutations in SMC1A have been reported in five females, all of whom have been affected by a drug‐resistant epilepsy, and severe developmental impairment. Our objective was to further delineate the phenotype of SMC1A truncation. Method: Female cases with de novo truncation mutations in SMC1A were identified from the Deciphering Developmental Disorders (DDD) study (n = 8), from postmortem testing of an affected twin (n = 1), and from clinical testing with an epilepsy gene panel (n = 1). Detailed information on the phenotype in each case was obtained. Results: Ten cases with heterozygous de novo mutations in the SMC1A gene are presented. All 10 mutations identified are predicted to result in premature truncation of the SMC1A protein. All cases are female, and none had a clinical diagnosis of CdLS. They presented with onset of epileptic seizures between <4 weeks and 28 months of age. In the majority of cases, a marked preponderance for seizures to occur in clusters was noted. Seizure clusters were associated with developmental regression. Moderate or severe developmental impairment was apparent in all cases. Significance: Truncation mutations in SMC1A cause a severe epilepsy phenotype with cluster seizures in females. These mutations are likely to be nonviable in males.